Analyzing the Impact of Quantum Computing on Current Encryption Techniques - Azhari, Rama; Salsabila, Agita Nisa (IAIC Transactions on Sustainable Digital Innovation (ITSDI), 2024)
As the field of quantum computing progresses, the disruption to traditional encryption methods, which secure vast amounts of sensitive data, becomes an imminent threat, and conventional encryption techniques, primarily based on mathematical complexity, may no longer suffice in the era of quantum supremacy. This research systematically analyzes the vulnerabilities of current encryption standards in the face of advanced quantum computing capabilities, focusing specifically on widely-used cryptographic protocols such as RSA and AES, which are foundational to modern cybersecurity. Employing the SmartPLS method, the study models the interaction between quantum computing power and the robustness of existing encryption techniques, involving simulating quantum attacks on sample cryptographic algorithms to evaluate their quantum resistance. The findings reveal that quantum computing possesses the capacity to significantly compromise traditional encryption methods within the next few decades, with RSA encryption showing substantial vulnerabilities while AES requires considerably larger key sizes to maintain security. This study underscores the urgency for the development of quantum-resistant encryption techniques, critical to safeguarding future digital communication and data integrity, and advocates for a paradigm shift in cryptographic research and practice, emphasizing the need for 'quantum-proof' algorithms. It also contributes to the strategic planning for cybersecurity in the quantum age and provides a methodological framework using SmartPLS for further exploration into the impact of emerging technologies on existing security protocols.